2009
DOI: 10.1557/proc-1208-o14-01
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Enhanced Fluorescence of Chlorophylls in Single Light-Harvesting Complexes

Abstract: Ensemble and single-molecule spectroscopy demonstrates that both emission and absorption of peridinin−chlorophyll−protein photosynthetic antennae can be largely enhanced through plasmonic interactions. We find up to 18-fold increase of the chlorophyll fluorescence for complexes placed near a silver metal layer. This enhancement, which leaves no measurable effects on the protein structure, is observed when exciting either chlorophyll or carotenoid and is attributed predominantly to an increase of the excitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 30 publications
3
43
0
Order By: Relevance
“…In all cases, the intensities measured for RCs on SIF are substantially higher than those on glass. Moreover, the distributions of fluorescence intensity values measured for RCs deposited on SIF substrates are significantly broader than those on glass, which points toward inhomogeneities attributable to local variations of plasmonic enhancement due to changes in SIF morphology or different distance between photosynthetic complexes and the metallic layer . Experimentally obtained average intensities of RC emission are listed in Table , together with EFs calculated by dividing the average values measured on SIF and glass.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In all cases, the intensities measured for RCs on SIF are substantially higher than those on glass. Moreover, the distributions of fluorescence intensity values measured for RCs deposited on SIF substrates are significantly broader than those on glass, which points toward inhomogeneities attributable to local variations of plasmonic enhancement due to changes in SIF morphology or different distance between photosynthetic complexes and the metallic layer . Experimentally obtained average intensities of RC emission are listed in Table , together with EFs calculated by dividing the average values measured on SIF and glass.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of PSI deposited on silver island films (SIFs), we recently found exceptionally large (~ 200) enhancement factors of the fluorescence intensity . Enhancements by two orders of magnitude are remarkable, in particular, when compared to the results obtained for other photosynthetic pigment–protein complexes, ranging from a factor of 2 to 20 . The effect appears to reflect the complexity of PSI, or, more specifically, the large number of bound pigments (chlorophylls and carotenoids).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…[ 117 ], the model was shown to be able to reproduce the experimentally determined amplification of the fluorescence signal for a LH protein (PCP) in the presence of silver nanoparticles. 119 More interestingly, the calculations allowed to gain insights into the role of metal to modulate the various involved optical processes (absorption, emission, EET between the pigments), and led to formulate design rules for building hybrid bio-nano-systems. Successively, the multilayer model was used to investigate how a plasmonic nanostructure affects excitonic states of the LH2 complex.…”
Section: Towards Composite Systemsmentioning
confidence: 99%
“…The effects of metals on fluorescence have been subject to prior reports. Using intrinsic(24), visible(25, 26, 28, 29) and NIR(27) fluorophores we have shown that the incident light-induced fields around the metallic nanoparticles can result in locally enhanced excitation, and the excited state fluorophores can crease plasmons in the particles, resulting in increased emission from the system of fluorophores and particles. We have shown proximity of fluorophores to metallic surfaces can increase the total radiative decay rate(31).…”
Section: Introductionmentioning
confidence: 99%